Olga Kovalets’. «Nen’ka Ukraine» - Kovalets’ , Olga (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. I am Ukrainian and I am proud of that. I am a patriot of my country. I read Ukrainian books, listen to Ukrainian songs, watch Ukrainian movies. My poem reflects the path of achievements of my Homeland. It was the history of my Ukrainian people that inspired me and I set out my thoughts on the paper. Ukraine has a very ancient history and culture. Many victories and failures. Independent Ukraine is a young country. We have a long way to go ahead. The young generation of Ukrainians is doing a lot for this. I sincerely believe that we will achieve everything we strive for! I want to share with you these videos about my amazingly beautiful Ukraine. Video: https://www.youtube.com/watch?v=WHeOZLmXxn8&feature=emb_title https://www.youtube.com/watch?v=vb0ZWc70gOk